Girl, Alone (An Ella Dark FBI Suspense Thriller-Book 1) - Blake, Pierce (Lukeman Literary, 2020)
"A MASTERPIECE OF THRILLER AND MYSTERY. Blake Pierce did a magnificent job developing characters with a psychological side so well described that we feel inside their minds, follow their fears and cheer for their success. Full of twists, this book will keep you awake until the turn of the last page." --Books and Movie Reviews, Roberto Mattos (re Once Gone) GIRL, ALONE (An Ella Dark FBI Suspense Thriller-Book 1) is the debut novel in a long-anticipated new series by #1 bestseller and USA Today bestselling author Blake Pierce, whose bestseller Once Gone (a free download) has received over 1,000 five star reviews. FBI Agent Ella Dark, 29, is given her big chance to achieve her life's dream: to join the Behavorial Crimes Unit. Ella has a hidden obsession: she has studied serial killers from the time she could read, devastated by the murder of her own sister. With her photographic memory, she has obtained an encyclopedic knowledge of every serial killer, every victim and every case. Singled out for her brilliant mind, Ella is invited to join the big leagues. But when a killer strikes in the swamps of Louisiana, Ella soon comes to learn that the real thing is nothing she could expect. Face to face with a real murder, a real killer, and a real ticking clock, Ella realizes she can't rely on her knowledge. She must learn to trust her instinct, and allow herself to enter the dark canals of a real killer's mind. If she gets it wrong, her career is at stake. And so is the next victim's life. Will Ella's talent be an asset? Or the source of her downfall? A page-turning and harrowing crime thriller featuring a brilliant and tortured FBI agent, the ELLA DARK series is a riveting mystery, packed with suspense, twists and turns, revelations, and driven by a breakneck pace that will keep you flipping pages late into the night. Books #2 and #3 in the series-GIRL, TAKEN and GIRL, HUNTED-are also available.
Keywords: Dobrodružství, napětí, thrillery; Krimi, detektivky